1982
DOI: 10.1002/1097-0142(19820715)50:2<219::aid-cncr2820500209>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for meningeal carcinomatosis in breast cancer

Abstract: Forty breast cancer patients with meningeal carcinomatosis were treated with a combined program of whole brain irradiation therapy with intrathecal and intraventricular methotrexate and citrovorum factor rescue. Responses were seen in 26 patients (65%); 13 patients (35%) failed to respond. The median survival time for the responding patients was six months, and for the nonresponders, one month. Factors affecting response and survival included pretreatment spinal fluid glucose, protein, and duration of CNS‐rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 9 publications
0
30
0
1
Order By: Relevance
“…First, CSF glucose levels and their prognostic meaning can be explained by the consumption of glucose by a mass of circulating tumor cells or by a widespread involvement of the meninges that may result in impaired transfer and, hence, may contribute to lower glucose concentrations. 14,16 Second, the meaning of RTOG neurological scores can be explained because they constitute a functional status scale 25,30 and, similar to the others, they are well known prognostic markers in cancer. [31][32][33] It is very likely that the use of the KPS would reinforce the results obtained with the RTOG scale regarding its prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, CSF glucose levels and their prognostic meaning can be explained by the consumption of glucose by a mass of circulating tumor cells or by a widespread involvement of the meninges that may result in impaired transfer and, hence, may contribute to lower glucose concentrations. 14,16 Second, the meaning of RTOG neurological scores can be explained because they constitute a functional status scale 25,30 and, similar to the others, they are well known prognostic markers in cancer. [31][32][33] It is very likely that the use of the KPS would reinforce the results obtained with the RTOG scale regarding its prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…There are weaknesses in the studies: Some have included in their series hematologic or primary brain tumors, they show important differences in sample size and analyzed variables, they have evaluated selected subsets of patients, and only univariate analyses were considered. 5,9,11,[13][14][15][16][17][18][19][20]22 Accordingly, currently, there are no useful prognostic markers, except for cerebrospinal fluid (CSF) blocks, 23,24 that could help clinicians to decide the best therapeutic approach for patients with LC. The objective of this study was to identify prognostic factors related to LC survival and enable clinicians to select patients who are more likely to benefit from chemotherapy treatment.…”
mentioning
confidence: 99%
“…Meningeal carcinomatosis is generally treated by intrathecal chemotherapy with MTX alone or in combination with Ara-C. [1][2][3][4][5] However, Bleyer 10) and Shapiro et al 11) have reported that when MTX is administered by lumbar puncture, the concentration of MTX that arrives at the subarachnoid space is low. In addition, Rieselbach et al 12) proposed that lumbar injections of Ara-C and MTX do not sufficiently distribute these drugs in the subarachnoid space of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] However, because maximum doses of MTX are limited by neurotoxicity, clinical results have not been satisfactory. 6) Recently a pilot study evaluating the efficacy and side effects of cerebrospinal fluid (CSF) perfusion chemotherapy with Ara-C and MTX in patients with meningeal carcinomatosis found that this therapy was effective in improving cerebral, cranial nerve and spinal root signs and symptoms.…”
mentioning
confidence: 99%
“…often combined with craniospinal irradiation. Carcinomatous meningitis [4,5] and astrocytomas [6] have also been similarly treated.…”
Section: Introductionmentioning
confidence: 99%